Synthesis and Screening of Substituted Chalcones as Lipoxygenase Inhibitors - Ahmed, Umair; Kaskhedikar, S.G.; Ahmad, Zafar; Ahmed, Shahzad (Asian Journal of Chemistry, 2011)
The present work involved the synthesis of chalcone derivatives, their characterization and in vitro evaluation for lipoxygenase inhibitory activity. The synthesis of chalcone derivatives was carried out in one step employing Claisen Schmidt condensation. Different substituted benzaldehydes viz., 3,4,5-trimethoxy benzaldehyde, ortho-, meta- and para-benzaldehyde, orthobromobenzaldehyde, ortho- and para-methyl benzaldehyde, para-nitro benzaldehyde were condensed with 1-acetonaphthone. Thus, eight substituted chalcones were synthesized. All synthesized chalcone derivatives show lipoxygenase inhibitory activity. IC70 values of compounds were in the range of 6.5093 × 10-2 mM to 1.52 × 10-14 mM. The compounds were evaluated for lipoxygenase inhibitory activity by direct measurement of absorption of spectrophotometric analysis using lyophilized soyabean lipoxydase enzyme. Most of the synthesized derivatives showed significant lipoxygenase inhibitory activity.